Techniques for corrosion monitoring - Yang, Lietai (CRC Press, 2008)
Corrosion monitoring technologies are a vital step in efforts to combat corrosion, which can have major economic and safety implications. This important book provides a comprehensive analysis of the range of techniques for corrosion monitoring. It includes practical applications and case studies. The first part of the book reviews electrochemical techniques for corrosion monitoring, such as polarization techniques, potentiometric methods, harmonic analysis, galvanic sensors and multielectrode systems. A second group of chapters analyses other physical or chemical methods of corrosion monitoring. These include gravimetric techniques, radioactivity methods, hydrogen permeation methods and rotating cage techniques. The third part of the book examines corrosion monitoring in special environments such as concrete and soil. A final group of chapters discusses case studies, including the ways that corrosion monitoring can be applied to engine exhaust systems, cooling water systems, pipelines and equipment in chemical plants. With its distinguished editor and international team of contributors, Techniques for corrosion monitoring will be a valuable reference guide for engineers, scientific and technical personnel who deal with corrosion in such sectors as automotive engineering, power generation and the petrochemical industry.